Left ventricular apical thin point. Issue 7 (July 1977) - Bradfield, J W; Beck, G; Vecht, R J
Abstract : The wall thickness of the apex of the left ventricle has been measured at its thinnest point in 60 adult hearts at necropsy. This measured 2 mm or less in 97% of them and 1 mm or less in 67%.